2008
DOI: 10.1159/000166614
|View full text |Cite
|
Sign up to set email alerts
|

The Meiotic Recombination Hotspots of Schizosaccharomyces pombe

Abstract: Meiotic recombination predominantly occurs at genomic loci referred to as recombination hotspots. The fission yeast, Schizosaccharomyces pombe, has proved to be an excellent model organism in which to study details of the molecular basis of meiotic recombination hotspot activation. S. pombe has a number of different classes of meiotic hotspots, indicating that a single pathway does not confer hotspot activity throughout the genome. The M26-related hotspots are a particularly well characterised group of hotspot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Meiotic crossovers tend to form at specific sites in the genome of most organisms (Buard and de Massy, 2007;Mezard, 2006;Pryce and McFarlane, 2009); these are known as recombination hotspots. In mammals, hotspots are typically regions of 1-2 kb that occur every 50-100 kb within the genome (Jeffreys et al, 2001;McVean, 2010;Myers et al, 2008).…”
Section: Control Of Meiotic Dsb Formationmentioning
confidence: 99%
“…Meiotic crossovers tend to form at specific sites in the genome of most organisms (Buard and de Massy, 2007;Mezard, 2006;Pryce and McFarlane, 2009); these are known as recombination hotspots. In mammals, hotspots are typically regions of 1-2 kb that occur every 50-100 kb within the genome (Jeffreys et al, 2001;McVean, 2010;Myers et al, 2008).…”
Section: Control Of Meiotic Dsb Formationmentioning
confidence: 99%
“…126). Further studies have identified several additional trans -acting factors that are required for activation, including several ATP-dependent chromatin-remodelling factors (including Gcn5, Snf22, Ada2 and Mst2, which activate, and Hrp1 and Hrp3, which act antagonistically) and the transcriptional repressors Tup11 and Tup12, which suppress recombination 127,128 . Further analysis has revealed that the CRE element ATGACGT is appreciably more effective when it resides in an 18-bp consensus element, GNVTATGACGTCATNBNC 63 .…”
Section: Figurementioning
confidence: 99%
“…[6] for recent review). The ade6-M26 allele promotes specifically meiotic (but not mitotic) recombination [7].…”
Section: Introductionmentioning
confidence: 99%